2018
DOI: 10.1017/cri.2018.14
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of ISIS Propaganda and Recruitment Activities Targeting the Turkish-Speaking Population

Abstract: The “Islamic State in Iraq and Syria” (ISIS) is the main source of instability, not only in Iraq and Syria, but also throughout the Middle East. The instability poses a danger for the other parts of the world because of the influx of foreign fighters to the region. Extremists have taken advantage of the continuing conflicts in Iraq and Syria, with Syria in particular serving as a magnet for thousands of foreign fighters from more than 90 countries. While most of these IS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 4 publications
0
6
0
4
Order By: Relevance
“…Lacking identification with their host culture, individuals may seek belonging elsewhere, leaving them vulnerable for indoctrination or cooptation. Indeed, research (Ozeren, Hekim, Elmas, & Canbegi, 2018) has shown that this is the exact avenue through which the militant network known as Daesh/ISIS (Islamic State of Iraq and Syria) attempts to recruit members. By offering a sense of identity and community, ISIS recruited potential members through social media which transcended geographical boundaries.…”
Section: Muslims Treated With Suspicionmentioning
confidence: 99%
“…Lacking identification with their host culture, individuals may seek belonging elsewhere, leaving them vulnerable for indoctrination or cooptation. Indeed, research (Ozeren, Hekim, Elmas, & Canbegi, 2018) has shown that this is the exact avenue through which the militant network known as Daesh/ISIS (Islamic State of Iraq and Syria) attempts to recruit members. By offering a sense of identity and community, ISIS recruited potential members through social media which transcended geographical boundaries.…”
Section: Muslims Treated With Suspicionmentioning
confidence: 99%
“…Some information sources can be referred as toxic sources or authors, when they pursue the goal of propaganda, manipulation, and imposition of their subjective and biased point of view. One contemporary example is the use of online propaganda by terrorist organizations, which aim to disseminate propaganda to the public and to increase their media presence in the society [48]. Moreover, the debate on social media and fake news has surfaced in the context of the American elections in 2016, what includes the dimension of cyber stability and an emerging non-traditional understanding of political stability [49].…”
Section: Understanding the Purpose Of Information And Analytical Systems In Public Administrationmentioning
confidence: 99%
“…An appropriate strategy is monitoring and dealing with the negative ones, as well as the implementation of departmental engagement offline. Complaints are directed at the very fact of problems, not at the employees [48]. It is possible to subdivide complaints into justified (associated with an unplanned or unknown fact that happened objectively) and expected (associated with a planned or already known fact).…”
Section: Categorizing News Feedsmentioning
confidence: 99%
“…Some scholars had been interested in studying he powerfulness of ISIS' language (Ozerena et al, 2018;Mahood and Rane, 2017;Wignell, et al, 2017;Vergani and Bliuc, 2015;and Georges, 2015). However, they were concerned with word analysis rather than grammar analysis.…”
Section: Introductionmentioning
confidence: 99%